UTILIZATION OF FERMENTED RICE BRAN TO INCREASED PERFORMANCE OF PIG - I G., MAHARDIKA; SUDIASTRA, I W. (Majalah Ilmiah Peternakan, 2017)
The research has been conducted which aims to analisys the effect of fermented rice bran to pig performance.Completly Randomize Design with 4 treatments and 4 replicates were used in this research. Treatment A: pig givenration containing rice bran without fermentation, treatment B: pig given ration containing 25% fermented rice bran,treatment C: pig given ration containing 50% fermented rice bran, and treatment D: pig given ration containing100% fermented rice bran. Observed variabels are: feed consumption, average daily gain, feed convertion ratio,digestability of nutrient dan digestible energy (DE). Results of this study concluded the used of fermented rice branincreased of growth and feed efficiency.